The Rhyacophila fasciata Group in Europe: Rhyacophila fasciata Hagen 1859 and formerly synonymized species (Trichoptera: Rhyacophilidae), with new description of Rhyacophila fasciata and Rhyacophila septentrionis McLachlan 1865 (stat. prom.). - Valladolid, María; Arauzo, Mercedes; Chertoprud, Mikhail V.; Chvojka, Pavel; Czachorowski, Stanisław; Dorda, Beatriz A.; Hinić, Jelena; Ibrahimi, Halil; Karaouzas, Ioannis; Krpač, Vladimir; Kučinić, Mladen; Lodovici, Omar; et al. (Zootaxa, 2021)
The presence and distribution of Rhyacophila fasciata Hagen 1859 in Europe were revised, based on bibliographic study, collection specimens, and new material collected in different countries. The status of formerly synonymized species, Rhyacophila ferruginea (Scopoli 1763) and Rhyacophila septentrionis McLachlan 1865 was also assessed. The type of R. ferruginea is missing, the taxon is still unidentified, and thus we propose Rhyacophila ferruginea as a nomen dubium. Morphological features and genetic evidence revealed that R. septentrionis differs from R. fasciata, so we propose to change its status to status resurrectus. We therefore include new descriptions of the different stages (larva, pupa, male, and female) of R. fasciata and of R. septentrionis, together with a molecular analysis based on mitochondrial cytochrome oxidase I (mtCOI) and ecological notes. The species R. coppai Oláh 2020 NEW SYNONYM and R. soreda Coppa & Oláh 2020 NEW SYNONYM are synonyms of R. sociata Navás 1916; the species R. kopasa Oláh & Coppa 2020 NEW SYNONYM and R. rova Oláh & Coppa 2020 NEW SYNONYM are synonyms of R. denticulata McLachlan 1879; the species R. matrensis Oláh & Szczęsny 2020 is probably a synonym of R. fasciata, so more study of this species is needed in order to confirm or deny that it is a valid species.